Does demand pressure on options explain movements in implied volatility? - Kilkku, Arto (My University, 2008)
The purpose of this study is to examine how options demand explains movements in implied volatility. The study takes a stock option approach and uses Barclays Plc. stock options to determine how stock options demand affects to corresponding implied volatility. The Barclays Plc. stock options behaviour can be seen as a reflection of stock options markets in the London International Futures and Options Exchange (LIFFE). The option demands ability to explain implied volatility changes is investigated in five different moneyness categories. The empirical part of this study contains the use of Cox, Ross and Rubinstein binomial tree option pricing model and bisection method to calculate option implied volatilities. The hypotheses used in the study are based on the option pricing theory of flat option supply curves and the effects of option demand pressure on implied volatility changes are tested with specified regressions and ordinary least squares (OLS) estimation method. The data set of this study contains tick- and end-of-day Barclays Plc. stock options data from 4 January, 2005 to 30 December, 2005. These options are traded in the London International Fi-nancial Futures and Options Exchange (LIFFE). The empirical results show that changes in stock option implied volatility are directly related to demand pressure from public order flow and especially changes in implied volatility are dominated by call option demand. As a result – the demand pressure moves stock option prices. The trading is also partly motivated by changes in expected future volatility, but price reversals of implied volatilities are an average as much as 47 percent.
Keywords: Options; implied volatility; demand pressure; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|